Prevalence and correlates of loneliness in the later life—insights from Longitudinal Ageing Study in India (LASI) Wave-1 - Priya Srivastava; Manushi Srivastava (Indian Journal of Psychiatry)
Context: Loneliness is a psychosocial problem that can affect anyone at any age in any circumstances, but it has become a serious issue of concern among the elderly. Aim: The present study aims to examine the overall and state and union-territories-wise prevalence of loneliness among India’s elderly population and exploring the correlates of loneliness in old age. Method: The study is based on secondary data from Longitudinal Ageing Study in India (LASI) Wave-1 (2017-2018) data collected from a total of 30,394 older adults aged 60 and above excluding missing responses. Frequent loneliness was measured using a single question asking how often you feel alone. Statistical Analysis Used: Descriptive statistics, the Chi-square test, and bivariate logistic regression were used to meet the objectives. The statistical significance was set at <0.05. Results: 13.4% of elderly reported frequent loneliness. The prevalence of loneliness among elderly was found to be maximum in Andaman and Nicobar Island and minimum in Tripura. Age, current marital status, region, religion, MPCE quintile, number of chronic conditions, number of Activities of Daily Living (ADL), and Instrumental Activities of Daily Living (IADL) difficulties, involvement in physical activity, involvement in yoga/meditation, number of social networks, participation in social activities, and involvement in leisure activities like reading books, watching TV, or using computer were found to be significantly associated with loneliness. Conclusion: Not being in a marital union, having more than two chronic conditions, more than two ADL and IADL difficulties, being physically inactive, non-involvement in Yoga/Meditation, and small social network are associated with higher loneliness.